2017
DOI: 10.1007/978-3-319-69926-4_19
|View full text |Cite
|
Sign up to set email alerts
|

Towards Understanding Startup Product Development as Effectual Entrepreneurial Behaviors

Abstract: Software startups face with multiple technical and business challenges, which could make the startup journey longer, or even become a failure. Little is known about entrepreneurial decision making as a direct force to startup development outcome. In this study, we attempted to apply a behavior theory of entrepreneurial firm to understand the root-cause of some software startup's challenges. Six common challenges related to prototyping and product development in twenty software startups were identified. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…(2) Criterion validity: Two previous studies [6,9], cf. Section 2, achieved similar results as our findings but relied on quantitative methods.…”
Section: A Threats To Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Criterion validity: Two previous studies [6,9], cf. Section 2, achieved similar results as our findings but relied on quantitative methods.…”
Section: A Threats To Validitymentioning
confidence: 99%
“…Agile and Lean Startup practices are also part of this process. A startup is recognized as a special condition for developing software products, in which the influence of business and team dimensions are more significant than those in traditional environments [4][5][6]. Software startup engineering (SSE) practices and their evolution cycle are well-explored in the literature [4].…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in several papers as candidates for inclusion. After assessing title, abstract, and finally the full text, 7 more papers were included as primary studies [17,28,29,44,45,46,47]. Among the papers, 21 were conference papers, five were journal papers, and one was a book chapter.…”
Section: Manual Searchmentioning
confidence: 99%
“…Many previous studies have reported combining interand multidisciplinary teams for realistic product creation through startup practices in an academic setting [1][2][3][4][5][6]. Software-intensive courses with a focus on minimum viable product (MVP) creation are also commonplace [7][8][9][10]; however, to the best of our knowledge, there has been no prior meticulous investigation of student skills and startup formation motivations incorporating external activities (i.e. Innovation Bootcamp) within experience-based courses.…”
Section: Introductionmentioning
confidence: 99%